Peppa Pig and the apple stand. - Astley, Neville; Baker, Mark, 1959- (Candlewick Entertainment, 2024)
It's a beautiful autumn day, and Peppa Pig is in the apple orchard with Mummy Pig, Daddy Pig, and George. Their tree is so full of apples--how will they get them all down? Daddy Pig has a great idea: on the count of three, everyone shake the tree! After counting how many apples are in their baskets (fifteen!), Peppa thinks up the perfect plan: she and her friends can set up an apple stand in the clubhouse window. When Mummy Pig comes by and buys two apples for two buttons, then Doctor Polar Bear buys three, how many apples will Peppa and friends have left to sell? Subtract, sell, and meet some friendly neighbors with Peppa--and get ready for a delicious surprise!